Synthesis of Ni nanoparticles by Femtosecond Laser ablation in liquids: structure and sizing - Muñetón Arboleda, David (2015)
Synthesis of nickel (Ni) nanoparticles (NPs) suspensions was performed using a 120 fs (femtosecond) pulse laser to ablate a Ni solid target in n-heptane and water. Analysis of structure, configuration, and sizing was carried out using different independent techniques, such as optical extinction spectroscopy (OES), atomic force microscopy (AFM), transmission electron microscopy (TEM), and electron diffraction (ED), which yield interrelated information. AFM microscopy allows determining the spherical shape and size distribution of the NPs in the obtained colloids, while TEM provides knowledge about shape, structure, and size distribution. ED allows identification of the different metal and metal oxide compositions as well as their crystallographic phase. On the other hand, OES gives information related to size distribution, structure, configuration, and composition. Interpretation of these spectra is based on Mie theory, which, in turn, depends on Ni dielectric function. For NP radii smaller than 3 nm, sizedependent free and bound electron contributions to the dielectric function must be considered. To account for the full size span, complete Mie expansion was used for optical extinction cross-section calculations. A theoretical analysis of the dependence of plasmon resonance of bare core and core−shell Ni NPs with core size and shell thickness provides insight about their spectroscopic features. For n-heptane, species like bare core Ni and hollow Ni NPs are found in the colloid, the latter being reported for the first time in this work. Instead, for water, the colloid contains hollow nickel NPs and nickel oxide in different core−shell configurations: Ni−NiO and NiO−Ni, the latter also being reported for the first time in this paper. In both cases, the size distribution agrees with that derived from TEM and AFM analysis. The formation of the oxide species is discussed in terms of oxidation−reduction processes during ablation. Possible mechanisms for the formation of hollow species are proposed.